A great and terrible beauty - Bray, Libba (Bray, Libba. Gemma Doyle trilogy, 2003)
After the suspicious death of her mother in 1895, sixteen-year-old Gemma returns to England, after many years in India, to attend a finishing school where she becomes aware of her magical powers and ability to see into the spirit world.